PROMENE MAKSIMALNOG POTENCIJALA SNAGE NA FLEKSORE ZGLOBA LAKTA POSLE ŠEST NEDELJNOG PROGRAMIRANOG VEŽBANJA SA MATRIKS METODOM - Vladimir Vuksanović (Montenegrin Sports Academy and Faculty for Sport and Physical Education, 2011)
This particular research is analyzing the changes of the maximal muscle power in the elbow joint, as well as the anthropometrical measures and biomechanical variable. The program for exercising performed in this research has a longitudinal character with duration of 6 weeks and two check points. This program was performed on 17 adolescents. Participant had a task do power exercises on Scot's bench, with individual weights using the matrix method (modified amplitude of movement) The analyses and result from the statistical operation (ANOVA'S/MANOVA'S) have shown positive changes at the participant's maximal power (22,4%), also at the tested angular speed (70,1%) as well as it has shown decreasing of the local body fat of the involved arm for 16,6% after six weeks of program. The results are in favor of the program for transformation of motorics capabilities and they are directly focused of modification of power component.